Discourse of Learning and the Learning of Discourse. Issue 5 (18th August 2018) - Goldman, Susan R.
ABSTRACT: Citizens in the 21st century must be able to engage in reading to learn from multiple sources in academic, professional, and personal life. Doing so requires specialized reading, critical thinking, and communicating practices. Project READI took up the challenge of designing and researching learning environments that would support adolescent students in building the requisite knowledge, strategies, and dispositions that comprise these 21st century competencies. The conceptual framework is reviewed and two illustrations of classroom enactments of the READI approach are presented, one in historical inquiry and the other in literary interpretation. The enactments exemplify the central role of discourse for learning in disciplinary content areas.